EDUKASI MASYARAKAT MEMBUAT KARYA DAUR ULANG SAMPAH MENJADI TAS - Gaparianti, Rani; Inul, Inul; Nafisa, Lidiya; Ankhofia, Nida; Adestira, Monica; Alfarizi, Ahmad Riziq; Salsabila, Salsabila; Wiransyah, Akmal; Akmal, Muhammad; Fauzan, Fauzan; Mutiara, Intan; Saputra, Bayu Dwi (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
Waste is a problem that is quite difficult to solve in Indonesia. This happens because people's habits as consumers always produce waste, especially plastic waste. Plastic is a material consisting of inorganic substances made from chemicals that are difficult to decompose and are dangerous for the environment (Ekonomis et al., 2017). Garbage is an environmental problem because its quantity and danger hinder the survival of living things. Creativity is a pretty good solution for processing plastic waste so that it can be reused. There are many ways to increase a person's creativity, one of which is handicrafts from plastic waste which can be used for handicrafts, such as pencil cases, shopping bags, room decorations, wallets, decorative lamps, baskets, etc. (Nasution et al., 2019 ). The method of implementing this program is education and training so that children become creative. This program is implemented in the form of providing knowledge about plastic waste and training children's creativity in recycling plastic waste. Activities were carried out offline in the residential area, East Kace Village. This program aims to reduce plastic waste in the community as part of the waste recycling program. This plastic waste recycling program is also carried out for elementary school children up to adults. Implementation of plastic waste recycling education and training programs by utilizing plastic cup waste which takes place in the community, which lasts for one day according to group agreement. This program aims to increase the sense of awareness and creativity in children. Before carrying out the program, student members held discussions with foundation administrators regarding plastic cup waste in the community. After conducting discussions, it was shown that the plastic waste in the residential area was not being utilized properly, and knowledge about processing plastic waste into crafts was very minimal. In the implementation of the craft making program which took place in the East Kace Residential Area, it was running smoothly and well. This is because there is a lot of enthusiasm from the student children who take part, as well as friends who continue to be enthusiastic and never give up in implementing and running this program. The conclusion obtained from this program is the increase in knowledge and creativity of children in the environment regarding plastic cup waste. Children's creativity increases because they can process and create plastic waste around them into items that can be reused and also have economic value.